PEMBELAJARAN ONLINE: PERSEPSI DAN PENERAPANNYA DI UNIVERSITAS MUHAMMADIYAH ACEH (Online Learning: Perception and Application at Muhammadiyah University Aceh) - Emawati Emawati (Jurnal Ilmiah Didaktika, 2022)
Curriculum development is a must in an educational institution. One way to develop the curriculum is through reformatting instructional process. During the covid-19, online learning becomes a must. For that reason, this qualitative research explores online learning process implemented in one of the private universities in Aceh. The data for the study were gathered through semi-structured interviews. The participants of the study were the dean of the Faculty of Islamic Education, the head of department of Islamic education, and a lecturer in the department. The result of this study suggests that online learning is inevitable in this Covid-19 pandemic; the lecturers are also found to have been capable in using online learning platforms: the lecturers are capable of using the general and a special-designed learning platform available. Curriculum development was conducted through several steps. Lecturers disseminate information about the use of online platform, they also make use of online learning available for students through online media, and finally all participants agree to prevent learning loss through encouraging students to be honest and accountable for what they do during their learning.